A study on ohsas 18001: 2007 implementation in tl offshore sdn bhd / Hairuddin Nasri - Hairuddin, Nasri (2018)
In an era of globalization and rapid development, the requirements of occupational health and safety management system in organizations is vital importance either to a small or large organization after occurrence multiple episodes of disasters and fatal accidents. The existence of this awareness has led many organizations to take a first step by governing their safety management system. The aim of this study is to identify the problems and benefits implementing OHSAS 18001 series in TL Offshore Sdn Bhd located in Seri Kembangan. Data was collected for this study through walk-through observation, audit findings using safety management system assessment checklist that was refer from the OHSAS 18000 standard. Interviews and discussions were carried out with the onshore and offshore management to prioritize recommendations made in improving occupational health and safety management on each site. From the walkthrough observation and audit safety management system assessment, most of the findings that have impact to implementation are being well-managed through various discussion and recommendation from other subsdiaries and also by client expectations by health and safety management system requirements. This study has fulfilled its aim and objectives. Future work recommendations could focus on to enhance new standardization such as ISO 45001 for TL Offshore and other subsidiaries in SapuraKencana Petroleum Berhad Group of Company.